2016
DOI: 10.1186/s13030-016-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cancer-related distress in Japan: a retrospective observation study

Abstract: BackgroundCancer care is currently the most important medical issue in Japan. Total pain of cancer patients consists of a combination of four factors: physical, psychological, social distress, and spiritual pain. Previous studies showed female cancer patients ask for more psychological support and seem to suffer different types of distress compared with male patients, for example, appearance-related symptoms. However, other factors of cancer distress related to gender have not been defined comprehensively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
6
32
1
Order By: Relevance
“…On the basis of this framework, we assumed that changes in appearance caused by OCC, and its treatment would lead to differences in internalization and representation between males and females. Previous studies of cancer patients indicated that poor physical function, greater emotional distress, poor psychosocial function, and female gender were negatively associated with body image satisfaction. These patients may also experience altered body image after treatment, although insufficient attention has been devoted to this important topic.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the basis of this framework, we assumed that changes in appearance caused by OCC, and its treatment would lead to differences in internalization and representation between males and females. Previous studies of cancer patients indicated that poor physical function, greater emotional distress, poor psychosocial function, and female gender were negatively associated with body image satisfaction. These patients may also experience altered body image after treatment, although insufficient attention has been devoted to this important topic.…”
Section: Introductionmentioning
confidence: 92%
“…An altered body image in cancer patients is associated with more physical symptoms, depression, lower global health status, more severe symptoms, and impaired psychosocial adjustment . Gender also affects the psychosocial adaptation and body image of cancer patients, in that females report greater psychological disturbances, more changes in appearance, and greater alterations in body image …”
Section: Introductionmentioning
confidence: 99%
“…For women, the areas that contribute to distress are psychosocial problems, such as changed self‐image, family‐related problems and sexual problems. Men more commonly have problems of an existential nature (Koyama et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many published studies have been conducted in non‐European settings, about distress and its effects on people with cancer, using the Distress Thermometer (Burgoyne et al, ; Koyama et al, ; Tonsing & Vungkhanching, ), some studies have also been conducted in Europe (Biddle et al, ; Jorgensen et al, ) but only a few in Sweden (Thalén‐Lindström et al, ), and none of the studies have had focused on working‐age patients; therefore, it is important to illuminate how distress is manifested in people with cancer of working age in a European country such as Sweden. Due to the consequences of treatment/illness, the target group is at risk for an extended reduced working capacity with accompanying financial worry.…”
Section: Introductionmentioning
confidence: 99%
“…Gender has long been viewed as a particularly important variable in psychosocial adaptation to HNC. Several studies have found that female patients have a greater psychological disturbance resulting from cancer than men …”
Section: Introductionmentioning
confidence: 99%